Incidence of Neonatal Hyperbilirubinemia based on Their Characteristics at Dr. Hasan Sadikin General Hospital Bandung Indonesia - Nurani, Namira Bening; Kadi, Fiva Aprillia; Rostini, Tiene (Althea Medical Journal, 2017)
Background: Hyperbilirubinemia is the most frequent clinical condition that occurs in neonates identified by yellow discoloration of the skin and other tissues. It is caused by elevations of bilirubin level as the effect of increased breakdown of red blood cells, impaired conjugation of indirect bilirubin, and incomplete bilirubin excretion. This study was conducted to discribe the characteristics of neonates with hyperbilirubinemia.Methods: This study used descriptive quantitative method which took retrospective data from medical record of neonates with hiperbilirubinemia in 2014. The population of this study was neonates which were born in the perinatology division at Dr. Hasan Sadikin General Hospital, Bandung. The variables collected were gender, gestational age, weight birth, general condition ad treatment options. The collected data were tabulated and presented by percentage and in the form of a table.Results: One hundred and seventy four of 230 medical records of neonates with hyperbilirubinemia were collected based on the inclusion criteria. The results showed that 8.04% of 2,531 neonates born at Dr. Hasan Sadikin General Hospital in 2014 suffered from hyperbilirubinemia. Males (56.9%) were higher than females to have hyperbilirubinemia. Neonates born at term gestational age (55.2%) were more likely to have hyperbilirubinemia with low birth weight category (51.7%), healthy general condition (60.4%). The most treatment option wasÂ phototherapy (54.6%).Conclusions: Most neonates with hyperbilirubinemia are males, who were born at aterm gestational age, with low birth weight. Most of the neonates are in healthy general condition and the most common treatment given to neonates is phototherapy.